Functionally graded materials - Mahamood, Rasheedat Modupe, 1973-; Akinlabi, Esther Titilayo, 1976- (Springer, 2017)
This book presents the concept of functionally graded materials as well as their use and different fabrication processes. The authors describe the use of additive manufacturing technology for the production of very complex parts directly from the three dimension computer aided design of the part by adding material layer after layer. A case study is also presented in the book on the experimental analysis of functionally graded material using laser metal deposition process.
Keywords: Functionally gradient materials.; elektronické knihy; electronic books